2021
DOI: 10.1039/d1qm00371b
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the surface area and CO2uptake of conjugated microporous polymersviaa post-knitting method

Abstract: Synthesis of high-surface-area porous organic polymers (POPs) for CO2 capture and storage (CCS) has obtained much attentions from researchers. However, construction of POPs with large surface area still remains challenging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 65 publications
1
22
0
Order By: Relevance
“…Liu et al synthesized four types of CMPs by Suzuki coupling reaction followed by crosslinking with HCPs by Friedel‐Craft alkylation. [ 90 ] The Suzuki coupling reactions were catalyzed by a palladium catalyst (Pd(PhCN) 2 Cl 2 ) to form four different types of CMPs. The reaction took place at 120°C for 3 days in the solvent phase (using dimethylformamide).…”
Section: Synthesis Methods Of Porous Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al synthesized four types of CMPs by Suzuki coupling reaction followed by crosslinking with HCPs by Friedel‐Craft alkylation. [ 90 ] The Suzuki coupling reactions were catalyzed by a palladium catalyst (Pd(PhCN) 2 Cl 2 ) to form four different types of CMPs. The reaction took place at 120°C for 3 days in the solvent phase (using dimethylformamide).…”
Section: Synthesis Methods Of Porous Materialsmentioning
confidence: 99%
“…The knitting agents are dimethoxymethane and dichloromethane. (Reproduced from Liu et al [ 90 ] with permission from the Chinese Chemical Society (CCS), Institute of Chemistry of Chinese Academy of Sciences (IC), and the Royal Society of Chemistry. )…”
Section: Synthesis Methods Of Porous Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 POPs have been used in many diverse applications in gas separation, 15,16 gas storage, 17 and gas detection. 18 POPs such as porous polymer networks (PPNs), 19 hypercrosslinked polymers (HCPs), 20,21 conjugated microporous polymers (CMPs), 22,23 porous aromatic frameworks (PAFs), 24,25 and polymers of intrinsic microporosity (PIMs) 26 are widely investigated. Out of these polymers, CMPs have the low preparation cost, large surface area, high thermochemical stability, low skeletal density, and synthetic diversity which make them a unique sorbent.…”
Section: Introductionmentioning
confidence: 99%
“…First, a combination of fine-tuned pore sizes, well-defined adsorptive sites, and remarkable physicochemical stability makes PCPs excellent materials for gas separation and storage. [15][16][17] It has been demonstrated that the adsorption capacity and selectivity can be improved by nanopore size engineering and the introduction of heterocycles or CO 2 -philic functional groups, [18][19][20][21] etc. In addition, PCPs have been proven to be a promising platform for CO 2 photoreduction because their electronic structures and band positions can be fine tuned at the molecular level to meet the requirements for artificial photosynthetic production of CO and hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%